2006
DOI: 10.1161/01.atv.0000225699.36212.23
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic Fluorescence and Diffuse Reflectance Spectroscopy Identify Superficial Foam Cells in Coronary Plaques Prone to Erosion

Abstract: Objective-Foam cells perform critical functions in atherosclerosis. We hypothesize that coronary segments with superficial foam cells (SFCs) situated in a region of interest with a depth of 200 m can be identified using intrinsic fluorescence spectroscopy (IFS) and diffuse reflectance spectroscopy (DRS). This is a key step in our ongoing program to develop a spectroscopic technique for real-time in vivo diagnosis of vulnerable atherosclerotic plaque. Methods and Results-We subjected 132 human coronary segments… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 33 publications
2
28
0
Order By: Relevance
“…[23][24][25][26][27][28][29][30][31][32][33][34] Fluorescence spectroscopy techniques have been shown to detect elastin, collagen, lipids, and other sources of autofluorescence in normal and diseased arterial walls as well as to characterize the biochemical composition of atherosclerotic plaques both ex vivo and in vivo. 19,22,24,[35][36][37][38][39][40][41] More recently, a few studies have reported the application of fluorescence techniques to the identification of plaque disruption, 39 detection of plaques with thin fibrous cap, 40 discrimination of lipid-rich lesions, 42 and detection of macrophage infiltration. 41,[43][44][45] All of these are considered features associated with plaque vulnerability.…”
Section: Fluorescence Lifetime Spectroscopy and Imaging: Techniques Amentioning
confidence: 99%
See 1 more Smart Citation
“…[23][24][25][26][27][28][29][30][31][32][33][34] Fluorescence spectroscopy techniques have been shown to detect elastin, collagen, lipids, and other sources of autofluorescence in normal and diseased arterial walls as well as to characterize the biochemical composition of atherosclerotic plaques both ex vivo and in vivo. 19,22,24,[35][36][37][38][39][40][41] More recently, a few studies have reported the application of fluorescence techniques to the identification of plaque disruption, 39 detection of plaques with thin fibrous cap, 40 discrimination of lipid-rich lesions, 42 and detection of macrophage infiltration. 41,[43][44][45] All of these are considered features associated with plaque vulnerability.…”
Section: Fluorescence Lifetime Spectroscopy and Imaging: Techniques Amentioning
confidence: 99%
“…19,22,24,[35][36][37][38][39][40][41] More recently, a few studies have reported the application of fluorescence techniques to the identification of plaque disruption, 39 detection of plaques with thin fibrous cap, 40 discrimination of lipid-rich lesions, 42 and detection of macrophage infiltration. 41,[43][44][45] All of these are considered features associated with plaque vulnerability. 1 Fluorescence measurements can be conducted as either steady state ͑spectrally resolved͒ or time resolved.…”
Section: Fluorescence Lifetime Spectroscopy and Imaging: Techniques Amentioning
confidence: 99%
“…Moreover, there is sound physical basis and justification for the agreement between spectroscopy and histology rather than simply statistical correlations. The algorithm for detecting NC /SFCs is consistent with previously published work, in which β-carotene from DRS was used to detect SFCs, 12 and the Raman contribution 9, 13, 24 was used to detect lipid pools. However, this is the first time that such an algorithm is proposed that utilizes both DRS and Raman spectral parameters in a joint classification.…”
Section: Spectral Correlation With Plaque Morphologymentioning
confidence: 69%
“…9 Independently, we have also shown the potential of diffuse reflectance spectroscopy (DRS) and intrinsic fluorescence spectroscopy (IFS) to detect plaque vulnerability features such as superficial foam cells. 12 By combining DRS, IFS, and Raman spectroscopy, a methodology we call multimodal spectroscopy (MMS), we can obtain even more detailed information about the disease state of the plaque. 13 The spectroscopic information provided by the three components of MMS is complementary and depth sensitive.…”
Section: Introductionmentioning
confidence: 99%
“…17 Angheloiu et al observed superficial foam cells in erosion-prone plaque. 18 Although depostion of proteoglycans and hyaluronan were not examined, frequent deposition of MF in the superficial layer indicates that the superficial lipid deposition group and the calcified cap subtype of yellow plaques were a pre-stage of erosion.…”
Section: Erosionmentioning
confidence: 99%